Nursing interventions to cover patients' basic needs in the intensive care context - A systematic review - Marie Hamilton Larsen; Gudrun Irene Johannessen; Kristin Heggdal (Wiley, 2022)
Abstract Aim To examine the content, theoretical frameworks and effectiveness of nursing interventions utilizing patient‐reported outcome measures (PROMs) in the intensive care unit (ICU). Design A systematic review and narrative synthesis following the guidelines of the preferred reporting items for systematic reviews and meta‐analysis checklist. Methods We searched the MEDLINE, CINAHL, PsycINFO, SweMed and Cochrane controlled trials register (CENTRAL) databases for studies evaluating interventions primarily delivered by nurses in the ICU. Two independent reviewers performed study selection, data extraction and risk of bias. Results Twenty‐two studies were included, whereas only seven studies used a theoretical framework. The interventions were heterogeneous in content, duration and choice of PROMs. Outcomes were related to covering patients' and families' basic needs, described by Henderson as essential functions of nursing. Several studies reported positive intervention effects, and nurses' communication and psychosocial care were considered essential components of nursing interventions in the ICU.